The catalytic domain CysPc of the DEK1 calpain is functionally conserved in land plants. (13th June 2013) - Liang, Zhe; Demko, Viktor; Wilson, Robert C.; Johnson, Kenneth A.; Ahmad, Rafi; Perroud, Pierre‐François; Quatrano, Ralph; Zhao, Sen; Shalchian‐Tabrizi, Kamran; Otegui, Marisa S.; Olsen, Odd‐Arne; Johansen, Wenche
Summary DEK1, the single calpain of land plants, is a member of the ancient membrane bound TML–CysPc–C2L calpain family that dates back 1.5 billion years. Here we show that the CysPc–C2L domains of land plant calpains form a separate sub‐clade in the DEK1 clade of the phylogenetic tree of plants. The charophycean alga Mesostigma viride DEK1‐like gene is clearly divergent from those in land plants, suggesting that a major evolutionary shift in DEK1 occurred during the transition to land plants. Based on genetic complementation of the Arabidopsis thaliana dek1‐3 mutant using CysPc–C2L domains of various origins, we show that these two domains have been functionally conserved within land plants for at least 450 million years. This conclusion is based on the observation that the CysPc–C2L domains of DEK1 from the moss Physcomitrella patens complements the A. thaliana dek1‐3 mutant phenotype. In contrast, neither the CysPc–C2L domains from M. viride nor chimeric animal–plant calpains complement this mutant. Co‐evolution analysis identified differences in the interactions between the CysPc–C2L residues of DEK1 and classical calpains, supporting the view that the two enzymes are regulated by fundamentally different mechanisms. Using the A. thaliana dek1‐3 complementation assay, we show that four conserved amino acid residues of two Ca2+‐binding sites in the CysPc domain of classical calpains are conserved in land plants and functionally essential in A. thaliana DEK1.